The growth of local white muscovy during starter and grower periods - Triana Susanti; Maijon Purba (Jurnal Ilmu Ternak dan Veteriner, 2017)
Livestock animals with relatively fast growth and great body weight are potential as a producer of meat. In Indonesia, the local muscovy, especially the feathered white is one of the meat-producing livestock. However, an analysis of the growth on local white muscovy is still rarely done. Therefore, the purpose of this study was to determine the point of inflection as growth variables, thus simplifying the preparation of development programs of local white muscovy. A total of 168 of the local unsex white muscovy were examined for their growth since the DOD until 112 days of age. The data of growth i.e. body weight individually examined in every two weeks. The data were analyzed using Gompertz model. The result obtained was the growth equation of local white Muscovy based on the model of Gompertz: Y=2591.3*exp (-3.8636*exp-0.0272*t). Based on these equations, the point of inflection of the local white muscovy occurred at the age of 50 days with a weight of 953.29 g. The maximum body weight gain achieved was 2591.30 g. It is conclude that the growth of local white muscovy was relatively slow, but the body weight was very heavy.